2001
DOI: 10.1073/pnas.041625098
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proacrosin binding protein sp32 precursor as a human cancer/testis antigen

Abstract: Serological expression cloning of antigens eliciting a humoral immune response to a syngeneic mouse sarcoma identified pem (mouse placenta and embryonic expression gene) as a new member of the cancer͞testis family. To identify the human homologue of pem, mouse pem sequences and pem-related expressed sequence tags from human testis were used as PCR primers for amplification using human testis cDNA. However, rather than pem, another gene, designated OY-TES-1, was isolated and found to be the human homologue of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
93
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 41 publications
1
93
1
Order By: Relevance
“…We have isolated and identified several CT and CT-like antigens, such as OY-TES-1, XAGE-1, AKAP3, RFX4 and TSGA10. 13,20,25,35,36 Our study added CCDC62-2 to the list of CT antigens for polyvalent cancer vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have isolated and identified several CT and CT-like antigens, such as OY-TES-1, XAGE-1, AKAP3, RFX4 and TSGA10. 13,20,25,35,36 Our study added CCDC62-2 to the list of CT antigens for polyvalent cancer vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…11 More recently, bioinformatics based analysis resulted in the cloning of BRDT, OY-TES-1, PAGE5, LDHC and TPTE. [12][13][14][15][16] Among these methods, SEREX seems to be effective for the identification of CT antigens. Using cDNA libraries from cancer or normal testis tissues, SSX2, SYCP-1, NY-ESO-1 and XAGE-1 were isolated.…”
mentioning
confidence: 99%
“…The testis-specific expression of CT antigens may prompt one to investigate whether previously defined sperm proteins are also expressed in tumors. We have been studying the expression in tumors of proacrosin binding protein sp32 precursor present in spermatozoa (22) and A-kinase anchoring protein 3 (AKAP3) present in the sperm head and flagellum (7). Real-time RT-PCR analysis using a TaqMan probe showed mRNA over-expression associated with those sperm proteins in some tumors compared to corresponding normal tissues.…”
mentioning
confidence: 99%
“…CT antigens are intriguing therapeutic targets for immunotherapy because of their limited expression in normal tissues and the fact that the testis and placenta are immune-privileged sites. However, the biological function and the relation to malignancy of most of these genes is unknown (Ono et al, 2001;Scanlan et al, 2002). Similarly, we do not yet know the biological function of CRG-L2.…”
Section: Crg-l2 Is Upregulated Early During Tumor Development But Is mentioning
confidence: 99%
“…Currently, there are more than 10 genes identified that are CT antigens, one of which, PAGE, also shows high expression levels in the placenta (Brinkman et al, 1998). Most CT antigens map to the X chromosome, but SCP-1 (Tu¨reci et al, 1998), CT9 (Scanlan et al, 2000), and OY-TES-1 (Ono et al, 2001) map to other chromosomes, as does CRG-L2. CT antigens are intriguing therapeutic targets for immunotherapy because of their limited expression in normal tissues and the fact that the testis and placenta are immune-privileged sites.…”
Section: Crg-l2 Is Upregulated Early During Tumor Development But Is mentioning
confidence: 99%